Immunomodulatory factors and infectious agents associated with the hepatic gene expression of the IGF system in nursery pigs. (27th February 2014) - Slifierz, M. J.; Friendship, R.; de Lange, C. F. M.; Slavic, D.; Grgic, H.; Farzan, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Recent findings suggest there is a complex interaction between the IGF system and the inflammatory immune response. The objective of this study was to determine whether gene expression of growth factors (IGF-1, IGF-binding protein-3 (IGFBP-3) and growth hormone receptors (GHR)) in the liver is associated with gene expression of immunomodulators in the liver, including C-reactive protein (CRP), serum amyloid A (SAA), haptoglobin (Hp), interferon-α (IFN-α), IFN-γ, tumour necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, IL-10 and IL-18, as well as with the presence of Salmonella spp., Lawsonia intracellularis, Brachyspira spp., enterotoxigenic Escherichia coli, methicillin-resistant Staphylococcus aureus, swine influenza virus, and porcine reproductive and respiratory syndrome virus (PRRSV) in nursery pigs (n=74) from commercial farms (n=4). Gene expression was quantified using reverse transcription quantitative-PCR (RT-qPCR) and the data were modelled using logistic regression methods. Pigs with elevated IGF-1 expression were less likely to have increased expression of TNF-α (odds ratio (OR)=0.14, P<0.01) and IL-18 (OR=0.19, P<0.05), and less likely to be colonized with PRRSV (OR=0.03, P<0.01). Pigs with increased expression of IGFBP-3 were more likely to have elevated IL-6 expression (OR=8.5, P<0.05). It was also observed that IGFBP-3 and IGF-1 were significantly associated when Hp expression was low (OR=30, P<0.05), but this association was not significant when Hp expression was high (P=0.54). Pigs with increased expression of GHR were less likely to have elevated expression of SAA (OR=0.01, P<0.05) and IL-1β (OR=0.03, P<0.05), but more likely to have increased expression of CRP (OR=290, P<0.01). Overall, there appears to be an inverse association between the hepatic expression of the IGF system (IGF-1, IGFBP-3, GHR) and certain cytokines (IL-1β, IL-18, TNF-α) and acute-phase proteins (SAA, Hp).